Identification of Matrix Metalloproteinase-12 as a Candidate Molecule for Prevention and Treatment of Cardiometabolic Disease - Melina Amor; Veronica Moreno-Viedma; Alisina Sarabi; Nicole G Grün; Bianca Itariu; Lukas Leitner; Irene Steiner; Martin Bilban; Keiichi Kodama; Atul J Butte; Guenther Staffler; Maximilian Zeyda; et al. (BMC, 2016)
Abstract Obesity is strongly associated with metabolic syndrome, a combination of risk factors that predisposes to development of the cardiometabolic diseases: atherosclerotic cardiovascular disease and type 2 diabetes mellitus. Prevention of metabolic syndrome requires novel interventions to address this health challenge. The objective of this study was to identify candidate molecules for the prevention and treatment of insulin resistance and atherosclerosis, conditions that underlie type 2 diabetes mellitus and cardiovascular disease, respectively. We used an unbiased bioinformatics approach to identify molecules that are upregulated in both conditions by combining murine and human data from a microarray experiment and meta-analyses. We obtained a pool of 8 genes that were upregulated in all the databases analyzed. This included well-known and novel molecules involved in the pathophysiology of type 2 diabetes mellitus and cardiovascular disease. Notably, matrix metalloproteinase 12 (MMP12) was highly ranked in all analyses and was therefore chosen for further investigation. Analyses of visceral and subcutaneous white adipose tissue from obese compared with lean mice and humans convincingly confirmed the upregulation of MMP12 in obesity at the mRNA, protein and activity levels. In conclusion, by using this unbiased approach, an interesting pool of candidate molecules was identified, all of which have potential as targets in the treatment and prevention of cardiometabolic diseases.